Lipid loses and barrier function modifications of the brown‐to‐white hair transition. Issue 4 (13th February 2019) - Oliver, Marc A.; Marti, Meritxell; Coderch, Luisa; Carrer, Victor; Kreuzer, Martin; Barba, Clara
Abstract: Background: The main objective of this study was to determine the lipid profile of brown and white Caucasian hair fibres and the effects of lipids on the properties of fibres. Materials and Methods: To determine the structures of white and brown hair lipid bilayers, cross sections of fibres of both hair types were examined using synchrotron‐based μ‐FTIR mapping. Dynamic vapour sorption (DVS) analyses were also performed to determine the differences in the barrier function of both fibres. Results: Spatial identification of lipids showed that a great amount of lipids was present in the medulla of fibres of both hair types, but important differences were also observed between cuticles of the different fibres. The cuticle of a white hair fibre showed a significant decrease in its lipid content, but did not show differences in the lateral packing order with respect to the cuticle of a brown hair fibre. The cortex and medulla of the white hair fibre also exhibited a significant decrease in its lipid content but with a higher lateral packing order than brown hair. Using DVS analysis, it was found that the water dynamics of white hair fibres differed from those of brown hair fibres, showing a decrease in their total capacity to absorb water and an increase in the velocity of the exchange of water with the environment. Conclusion: The results of both techniques demonstrated a high correlation between the characteristics of the lipids located in the cuticle and the water dynamics of the fibres.